The Function and Context of Speaking in the Oral Tradition of the Kejhung Madura : A Sociopragmatic Study - Sri Utami; Widayati, Wahyu; Victor Marolitua L Tobing (HM Publisher, 2022)
The purpose of this study is the function of speech acts in the Madurese kejhung oral tradition and the context behind the Madurese kejhung oral tradition, which includes situation, social, culture, and ideology. This study uses a sociopragmatic approach and descriptive method. Researchers as human instruments. This research involves hermeneutic and sociopragmatic analysis methods. Hermeneutics is used to reveal the conditions of the context. This study uses data in the form of kejhung text which contains the function of speech and the context of the Madurese kejhung oral tradition in the form of rhymes. The results of the study indicate that the speech function is dominated by the directive speech function, both the advisory directive function and the inviting or wishing directive function. This shows that the function of Madurese speech is to actualize the attitude of the Madurese. The context of the kejhung madura situation is the wedding ceremony, welcoming guests, cow race, sonok cow, and rokat tase'. The social context behind daily life such as harmony and cooperation, the cultural context is the customs and way of life, while the ideological context behind the Madura kejhung is strong Islamic teaching within the Madurese community.